Chapter 3 Multiple Marginalizations Based on Age: Gendered Ageism and Beyond (2018)
This chapter offers a theoretical contribution to the discussions revolving around multiple marginalizations based on age. Our main focus is on gendered ageism, where vulnerability and marginalization is based on the interaction of age and gender, and its potential to highlight the processes and practices of marginalization. Based on the understanding of ageism as a socio-cultural practice involving privilege, subordination, and inequality, we rework existing conceptualizations of multiple marginalizations and of gendered ageism. The understanding of ageism as a form of doing enmeshed in interlocking power structures draws attention to the importance of socio-cultural context and the dynamics involved in the creation and reproduction of social reality, including social inequalities. This chapter draws on a wide range of existing studies to illustrate and explain this new approach. It concludes with an outline of an applicable research programme that yields novel ways of exploring multiple inequalities in later life and gendered ageism more specifically.